A Cervical Nerve Root Cavernoma – Atypical Presentation With Diagnostic Dilemma: Atypical Presentation With Diagnostic Dilemma - Moolchandani, Sandeep; Tyagi, Gaurav; Yagnick, Nishant; Sinha, Sumit; Mehta, Veer Singh (International Clinical Neuroscience Journal, 2023)
Background Spinal cavernous angiomas are uncommon vascular malformations in spine accounting for 5-12% of all spinal vascular lesions. When present in intradural extra-medullary location, these usually present with radicular pain and neurological deficits due to mass effect (myelopathy). We here present an atypical presentation of cavernous angioma in a 54-year-old male with tinnitus, headache and sensorineural hearing loss. We have also reviewed 51 cases of intradural extramedullary cavernous angiomas including our case with respect to demographic and clinical profile. Case Description A 54-year-old male presented with tinnitus in left ear and occipital headache with neck pain and slight weakness of left-hand grip along with atrophy of thenar muscles. His PTA examination revealed mild left sensorineural earing loss. MRI of cervical spine showed T2WI heterogeneously hyperintense left intradural extramedullary lesion at C7 vertebral body level. It was avidly enhancing with contrast. Patient underwent C7 laminectomy with a midline durotomy and complete excision of the lesion under neuromonitoring with sacrifice of the C8 sensory root. His symptoms improved following the surgery. Conclusions Spinal nerve root cavernomas are extremely rare. They usually present with radicular or myelopathy symptoms due to compression. Repeated rupture or micro-bleeds can cause raised intracranial pressure features along with cranial nerve deficits. The diagnostic workup is not straight forward in these latter cases and the presence of cavernoma may be an unusual finding. The diagnosis of a cavernoma in an unusual location in the presence of cranial nerve dysfunction needs a high degree of diagnostic suspicion. Majority of these cavernomas have a nerve root origin or attachment. The optimal treatment is microsurgical en bloc resection which leads to an effective resolution of both the symptoms.